3,4-Dimethylpyrano[2,3-c]pyrazol-6(2H)-one - Shahid, Bilal (International Union of Crystallography, 2012)
The asymmetric unit of the title compound, C(8)H(8)N(2)O(2), comprises two independent molecules in both of which, all non-H atoms lie in a common plane (r.m.s. deviation = 0.014 and 0.017 Å). In the crystal, N—H⋯O hydrogen bonds connect the molecules into zigzag chains running along [10-1]. Weak C—H⋯O interactions connect the chains into an infinite network.